MYCORRHIZAL COLONISATION ENHANCE THE GROWTH AND NUTRIENT UPTAKE IN DIFFERENT CROPS GROWN IN GLASSHOUSE PENGKOLONIAN MIKORIZA MENINGKATKAN PERTUMBUHAN DAN PENGAMBILANNUTRISI PADA BERAGAM TANAMAN DI RUMAH KACA - Barus, Henry Novero (Pembangunan Pedesaan, 2006)
This study aimed to investigate mycorrhizal colonisation on plant growth and nutrient acquisitions on three crop species, i.e, soybean (Glycine max (L.) Merr cv. Willis), upland rice (Oryza sativa cv. Cirata), and maize (Zea mays cv. Marshall). These crops were inoculated with arbuscular mycorrhiza fungi (AMF) Glomus mosseae BEG 107 grown in a Luvisol (Calcareous soil, pH 7.3 in CaCl2) under glasshouse conditions. Inoculated plants became mycorrhizal while control plants remained non-mycorrhizal. The AM colonisation rates were as high as 60%, 40%, 70% of the total root length, respectively, in soybean, upland rice, and maize. Mycorrhizal crop growth increased 7.5-folds, 4.5-folds, and 5.0-folds relative to non-mycorrhizal crop, respectively, in soybean, upland rice, and maize. Related to nutrient uptake, mycorrhizal colonisation increased P concentrations in shoot 1.6- folds, 3.2-folds, and 1.6-folds; and in root 1.9-folds, 1.9-folds, and 2.6-folds, respectively, in soybean, upland rice, and maize. However, it increased, decreased or were similar with other elements depended on elements and crop species. Applied mycorrhizal clearly contributed to enhance the growth and nutrient uptake of crop tested.